Aggressive interactions among female, semi‐captive pampas deer (Ozotoceros bezoarticus) increase within the hierarchy and after short‐term removal of the male. Issue 2 (12th February 2020) - Villagrán, Matías; Freitas‐de‐Melo, Aline; Bartoš, Luděk; Ungerfeld, Rodolfo
Abstract: Two trials were carried out to determine: (a) if there is a positive relation between the frequency of aggressive interactions among female pampas deer and their position within the hierarchy (HI), (b) if short‐term removal of the male triggers an increase in the frequency of aggression, and (c) if the magnitude of this increase is related to the individual rank position of the female. Each of 19 breeding groups comprised one adult male and from four to six adult females. The HI was determined for each female and all aggressive interactions were recorded. These were recorded while the male was present (i.e., all of Trial 1 and the "with male" period in Trial 2) and after removal of the male (i.e., the "without male" period in Trial 2). The individual percentage change in the frequency of aggressive interactions after male removal was calculated. In Trial 1 the HI, the frequency of different types of aggressive interaction and the total of aggressive interactions were positively related (all: p  < .001; General Linear Mixed Model [GLMM]). In Trial 2, the frequency of total aggressive interactions increased after male removal ( F (1, 27) = 3.5; p  < .001; GLMM). The individual percentage changes in aggressive interaction between periods were positively related to HI ( F (6, 24) = 2.56; p  = .05; GLMM). For female pampas deer maintained in breeding groups, we conclude that the frequency of aggressive interactions increases within the hierarchy. Aggression also increases after the short‐term removal of the male, mainly among females of higher social status.